2009
DOI: 10.1002/adma.200901035
|View full text |Cite
|
Sign up to set email alerts
|

Free‐Standing Biodegradable Poly(lactic acid) Nanosheet for Sealing Operations in Surgery

Abstract: A free-standing biodegradable nanosheet composed of poly(L-lactic acid) (PLLA) was shown to have excellent sealing efficacy for a gastric incision as a novel wound dressing material that did not require adhesive agents, and the PLLA nanosheet-induced wound repair showed neither scars nor tissue adhesion. This material may, therefore, be an ideal alternative to conventional tissue repairing procedures using suture/ligation in surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
217
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(225 citation statements)
references
References 29 publications
7
217
0
1
Order By: Relevance
“…In the case of the PLLA nanosheet-coated sample, the C1s peak was split into three subpeaks, representing the C-H signal of the methyl group at 284.0 eV, the C-O signal at 285.9 eV, and the C ¼ OO signal of the carboxylic group at 288.4 eV. These subpeaks were consistent with the characteristic molecular structures of PLLA, 15,29 supporting the presence of PLLA in the surface layer. From these results, we concluded that the modified PDMS surface was almost completely covered by the fragmented PLLA nanosheets.…”
Section: A Characterization Of the Modified Surfacessupporting
confidence: 58%
See 2 more Smart Citations
“…In the case of the PLLA nanosheet-coated sample, the C1s peak was split into three subpeaks, representing the C-H signal of the methyl group at 284.0 eV, the C-O signal at 285.9 eV, and the C ¼ OO signal of the carboxylic group at 288.4 eV. These subpeaks were consistent with the characteristic molecular structures of PLLA, 15,29 supporting the presence of PLLA in the surface layer. From these results, we concluded that the modified PDMS surface was almost completely covered by the fragmented PLLA nanosheets.…”
Section: A Characterization Of the Modified Surfacessupporting
confidence: 58%
“…15 In this study, we examined the long-term durability of the nanosheet-coated microchannel under dynamic flow conditions. As shown in Figure 4(b), the coverage ratio remained nearly unchanged, even after undergoing quite high shear stresses of 10.7 dyn/cm 2 and 21.3 dyn/cm 2 for an extended duration.…”
Section: B Microchannel Coatingmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies from the laboratory of Shinji Takeoka demonstrate excellent sealing efficacy of a poly-L-lactic acid (PLLA) nanofilm for gastric incisions as a novel wound dressing material that did not require adhesive agents, induce scars or adhere to surrounding tissues (7). This same group also demonstrated the efficacy of PLLA sheets as a method for fixing a polypropylene mesh in the peritoneal cavity without inducing visceral adhesions during open surgery (8).…”
Section: Introductionmentioning
confidence: 66%
“…[5][6][7][8] They are also used for fundamental studies exploring the behavior of polymers under confinement. [9][10][11][12][13] A free-standing film is one that is supported on a non-continuous substrate such as an annular ring or hoop as opposed to a silicon wafer or glass slide.…”
Section: Introductionmentioning
confidence: 99%